Between “ghettos”, “safe spaces” and “gaytrification” - Pedro Costa; Paulo Pires (Cidades, Comunidades e Território, 2019)
In recent decades, “LGBT neighbourhoods” or “gay Villages” have been gaining some prominence and particular characteristics within cities, representing safe spaces for the expression and negotiation of individual and collective identities as well as for the political affirmation of LGBT communities and queer identities. As other areas that have been the main drivers of urban revitalization of inner-cities, such as cultural and creative quarters or multicultural spaces, these territories distinguish for the social practices of their users and inhabitants, the specificities of their economic activity, or their contribute to creativity or social integration. More than community ghettos, these areas have been characterized by their openness and vibrancy, enhancing the coexistence of diverse lifestyles, trajectories and identities, but also by the contribution of LGBT people to the gentrification of these districts through their strong commercial, residential and symbolic presence.Drawing upon an empirical work developed in Lisbon (Príncipe Real district) and Madrid (Chueca district), based on in-depth interviews to LGBT residents and participant observation in the two neighbourhoods, this paper characterizes the main evolutionary trajectories and specificities of these two districts. An analysis is made confronting the characteristics and contingencies of these areas with other cases previously studied in literature, identifying the existence of notable differences and suggesting evidence of significant specificities, which can represent a “South European” approach to the reality of “Gay Villages”. Some generic principles for urban planning are drawn out from the analysis.